The Mediating Role of Entrepreneurial Capabilities in the influential relationship of strategic orientation in high performance: An analytical study of the opinions of a sample of members of college councils in private universities in the Kurdistan Region of Iraq - Salm Tofiq, Kaywan; Ibrahim Wali, Ahlam (Iraqi Journal for Administrative Sciences, 2026)
The research aims to diagnose the relationship between strategic orientation, with its dimensions (responsive, analytical, defensive, exploratory or proactive, and future orientation), and high performance, represented by (management quality, employee quality, continuous improvement and renewal, openness and work orientation, and long-term commitment), while testing the mediating role of entrepreneurial capabilities, including (proactive, relational, conceptual, organizational, and strategic capabilities). The study covered private universities in the Kurdistan Region of Iraq, based on a random sample of 120 college council members, with 107 valid questionnaires analyzed using the descriptive-analytical method and the (SPSS V26) program. The results showed that entrepreneurial capabilities are the most influential factor in achieving high performance, confirming the importance of dynamic and entrepreneurial capabilities in institutional excellence. The research recommends that private universities adopt an institutional strategy to strengthen entrepreneurial capabilities by establishing specialized units for entrepreneurship and innovation, training academic and administrative staff in entrepreneurial thinking, and supporting innovative projects through internal development and funding programs.